2021
DOI: 10.3390/vaccines9070793
|View full text |Cite|
|
Sign up to set email alerts
|

Next Generation of Computationally Optimized Broadly Reactive HA Vaccines Elicited Cross-Reactive Immune Responses and Provided Protection against H1N1 Virus Infection

Abstract: Vaccination is the best way to prevent influenza virus infections, but the diversity of antigenically distinct isolates is a persistent challenge for vaccine development. In order to conquer the antigenic variability and improve influenza virus vaccine efficacy, our research group has developed computationally optimized broadly reactive antigens (COBRAs) in the form of recombinant hemagglutinins (rHAs) to elicit broader immune responses. However, previous COBRA H1N1 vaccines do not elicit immune responses that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 50 publications
0
44
0
Order By: Relevance
“…For the nasal cavity, ferret heads were removed and fixed in neutral buffered 10% formalin and subjected to decalcification in Kristensen’s solution. Tissues were subsequently processed, embedded in paraffin, sectioned at 5 μm, and stained with hematoxylin and eosin (H&E) as described before ( 62 ). Histopathological evaluation of lungs and nasal cavities was performed by a board-certified pathologist.…”
Section: Methodsmentioning
confidence: 99%
“…For the nasal cavity, ferret heads were removed and fixed in neutral buffered 10% formalin and subjected to decalcification in Kristensen’s solution. Tissues were subsequently processed, embedded in paraffin, sectioned at 5 μm, and stained with hematoxylin and eosin (H&E) as described before ( 62 ). Histopathological evaluation of lungs and nasal cavities was performed by a board-certified pathologist.…”
Section: Methodsmentioning
confidence: 99%
“…Porcine intestinal tissue was purchased from Lampire Biological Products (Pipersville, PA). The recombinant COBRA HA protein (designed for the H1N1 influenza subtype) was produced by Ted Ross’ laboratory at the University of Georgia …”
Section: Methodsmentioning
confidence: 99%
“…The recombinant COBRA HA protein (designed for the H1N1 influenza subtype) was produced by Ted Ross' laboratory at the University of Georgia. 21 PEI-Ox-DEX Gel Fabrication. Dextran (71 kDa) was modified with aldehyde groups via periodate oxidation to form oxidized dextran (Ox-DEX).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Reneer et al, constructed an H2 COBRA HA vaccine and tested it in ferrets immunized against H2N3 attack, resulting in vaccinated ferrets exhibiting higher antibody titers and recognizing the highest number of H2 influenza viruses in a classical neutralization assay compared to wild-type H2 HA recombinant proteins [ 50 ]; Huang et al, used the COBRA approach to generate two new candidate COBRA HA vaccines, Y2 and Y4, from H1N1 isolates prevalent during 2013–2019. Mice vaccinated with Y2 and Y4 effectively reduced morbidity and mortality after infection with H1N1 influenza viruses, and vaccine-initiated antibodies associated with H1N1 isolates from 2009 to 2021 and pdm09-like viruses produced a high degree of cross-reactivity, with the strongest intensity of cross-reactivity in 2019–2021 [ 51 ]; Allen et al, first infected ferrets with three historical H3N2 species and then tested for expanded immune breadth with constructed COBRA or wild-type (WT) H3 VLP vaccine antigens and showed that, compared to the WT group, the COBRA group in all three historical H3N2 strains produced more cross-reactive antibodies and induced antibodies capable of neutralizing live virus infections of modern drifting H3N2 strains at higher titers [ 52 ].…”
Section: Development Of Universal Influenza Vaccinementioning
confidence: 99%